2016
DOI: 10.1002/jbm.a.35673
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an injectable thermoresponsive hyaluronan hydrogel in a rabbit osteochondral defect model

Abstract: Articular cartilage displays very little self-healing capabilities, generating a major clinical need. Here, we introduce a thermoresponsive hyaluronan hydrogel for cartilage repair obtained by covalently grafting poly(N-isopropylacrylamide) to hyaluronan, to give a brush co-polymer HpN. The gel is fluid at room temperature and becomes gel at body temperature. In this pilot study HpN safety and repair response were evaluated in an osteochondral defect model in rabbit. Follow-up was of 1 week and 12 weeks and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…64,65 For REVIEW ARTICLE JOURNAL OF BIOMEDICAL MATERIALS RESEARCH A | MONTH 2018 VOL 00A, ISSUE 00 example, additional hydrophobic groups resulting from copolymerization lead to lowering of LCST. 65 The most commonly used thermogels in cartilage tissue engineering are PluronicsV R , 66 p(NIPAAm) 67 and chitosan/ glycerol phosphate 68 very often grafted or blended with gelatin, 69 hyaluronic acid, 70 and chitosan. 49 Based on the literature review, it can be seen that common approach is using thermoresponsive base, such as p(NIPAAm) or PluronicV R with addition of natural polymer, such as hyaluronic acid for improvement of cellular response.…”
Section: Physical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 For REVIEW ARTICLE JOURNAL OF BIOMEDICAL MATERIALS RESEARCH A | MONTH 2018 VOL 00A, ISSUE 00 example, additional hydrophobic groups resulting from copolymerization lead to lowering of LCST. 65 The most commonly used thermogels in cartilage tissue engineering are PluronicsV R , 66 p(NIPAAm) 67 and chitosan/ glycerol phosphate 68 very often grafted or blended with gelatin, 69 hyaluronic acid, 70 and chitosan. 49 Based on the literature review, it can be seen that common approach is using thermoresponsive base, such as p(NIPAAm) or PluronicV R with addition of natural polymer, such as hyaluronic acid for improvement of cellular response.…”
Section: Physical Methodsmentioning
confidence: 99%
“…The most commonly used thermogels in cartilage tissue engineering are Pluronics®, p(NIPAAm) and chitosan/glycerol phosphate very often grafted or blended with gelatin, hyaluronic acid, and chitosan . Based on the literature review, it can be seen that common approach is using thermoresponsive base, such as p(NIPAAm) or Pluronic® with addition of natural polymer, such as hyaluronic acid for improvement of cellular response.…”
Section: Injectable Hydrogels In Cartilage Engineeringmentioning
confidence: 99%
“…In the study by D’Este et al, 37 biocompatibility and ease of use were confirmed, as the gel was injected into the site of the defect. Gel shearing from the nanotopographical surface could present a potential limitation of this construct upon scaling-up.…”
Section: Discussionmentioning
confidence: 93%
“…37 The addition of cells to the hydrogel led to a decrease of storage modulus after the transition. This is to be expected because the gelation mechanism is based on non-covalent interactions prone to disruption by the presence of MSC, especially at such a high concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation